Embracing Colonizations: A New Paradigm for Species Association Dynamics. (January 2018) - Nylin, Sören; Agosta, Salvatore; Bensch, Staffan; Boeger, Walter A.; Braga, Mariana P.; Brooks, Daniel R.; Forister, Matthew L.; Hambäck, Peter A.; Hoberg, Eric P.; Nyman, Tommi; Schäpers, Alexander; Stigall, Alycia L.; et al.
Abstract : Parasite–host and insect–plant research have divergent traditions despite the fact that most phytophagous insects live parasitically on their host plants. In parasitology it is a traditional assumption that parasites are typically highly specialized; cospeciation between parasites and hosts is a frequently expressed default expectation. Insect–plant theory has been more concerned with host shifts than with cospeciation, and more with hierarchies among hosts than with extreme specialization. We suggest that the divergent assumptions in the respective fields have hidden a fundamental similarity with an important role for potential as well as actual hosts, and hence for host colonizations via ecological fitting. A common research program is proposed which better prepares us for the challenges from introduced species and global change. Trends: Parasites are typically assumed to be highly specialized on their hosts and well adapted to them, yet they frequently colonize new hosts – including humans, causing EIDs. This parasite paradox has caused a growing unease with the traditional assumptions in parasitology, which differ markedly from those in the field of insect–plant studies. We report the results of a workshop where parasitologists and insect–plant researchers met to explore the possibility that the two systems may be more similar than the divergent research traditions suggest, so that a common research program can be developed to better prepare us for future challenges.